What's New in Idiopathic Clubfoot?. Issue 6 (September 2015) - Zionts, Lewis E.
Abstract : This update summarizes selected research highlights pertaining to idiopathic clubfoot deformity that were published in peer-reviewed journals between January 2010 and December 2013.